Aromatic chloroosmacyclopentatrienes. Issue 3 (28th October 2022) - Chu, Zhenwei; He, Guomei; Shi, Chuan; Hua, Yuhui; Huang, Yaxi; Chen, Jiangxi; Xie, Hujun; Jia, Guochen
ABSTRACT: Aromatic metallacycles are of considerable current interest. Reported aromatic metallacycles are mainly those with carbon, nitrogen, oxygen and sulfur. In this work, we report the synthesis and characterization of aromatic chloroosmacyclopentatrienes, which represent the first structurally confirmed metallaaromatic with a chlorine atom in its framework. Single-crystal X-ray diffraction studies show that these planar chloroosmacyclopentatrienes possess a very short Os–ClC distance suggesting M=ClC bond character. Abstract : Metal-chlorine bonds of halocarbon complexes are usually longer than metal-halide bonds. By contrast, this work demonstrates that complexes LnOsCl(ClR) have the Os−ClR bond shorter than the Os−Cl bond.